Organogenesis from leaf and internode explants of Ophiorrhiza prostrata, an anticancer drug (camptothecin) producing plant - Beegum, A. Shahanaz; Martin, Kottackal Poulose; Zhang, Chun-Lai; Nishitha, I. K.; Ligimol; Slater, Adrian; Madhusoodanan, P. V. (Electronic Journal of Biotechnology, 2007)
Camptothecin (CPT) analogues and derivatives serve as a novel class of effective anticancer agents that exert their action against DNA topoisomerase I. This paper presents procedures for the rapid, high frequency regeneration of a camptothecin producing plant, Ophiorrhiza prostrata D. Don from leaf and internode explants via shoot organogenesis. The concentrations of plant growth regulators and explant types exhibited discrete roles in the efficacy of shoot induction. N6-benzyladenine (BA) was the most effective cytokinin for the induction of shoots. Murashige and Skoog (MS) medium with 8.87 µM BA and 2.46 µM indole-3-butyric acid (IBA) yielded the highest number of shoots from leaf and internode explants (76.0 and 90.8 shoots respectively). In the case of leaf explants, explants from the proximal end produced a higher number of shoots than those from the mid and distal end. Leaf and internode explants cultured on MS medium supplemented with α-naphthaleneacetic acid (NAA) and BA developed shoots, calli and roots. Calli subcultured onto medium supplemented with 8.87 µM BA and 2.46 µM IBA developed a mean of 20.1 shoots within 40 days. Excision and culture of internode and proximal leaf explants from the established cultures on MS basal medium significantly enhanced the number of shoots and yielded a mean of 18.3 and 13.7 shoots respectively within 40 days. Histological examination of leaf explants showed that the shoots were of sub-epidermal origin, confined to the sub-epidermal cells above the vascular traces. Shoots cultured on half-strength MS basal medium with 10.74 µM NAA and 2.32 µM Kn produced a mean of 48.2 roots per shoot. Direct transfer of rootless healthy shoots showed a 50% survival rate, whilst it was 100 percent in the case of in vitro rooted shoots.